Peran Citra Merek, Nilai Pelanggan, dan Kualitas Persepsian terhadap Kepuasan Pelanggan: Sebuah Studi Kasus - Andriya Risdwiyanto; Saktya Ganes Saputra (Jurnal Maksipreneur, 2016)
Customer satisfaction is a key to the success of the company. Customer satisfaction has a positive relationship with the company's value for shareholders. By providing satisfaction to the customers, companies can gain greater market share and increase its profits. Some of the critical success factors in creating satisfaction for its customers include brand image, customer value, and perceived quality. This research revealed a significant role of brand image, customer value, and perceived qualityto customer satisfaction of Smartfren data service in Sleman, Yogyakarta.